Global research landscape on the crosstalk between ferroptosis and musculoskeletal diseases: A bibliometric and visualized analysis - Siyang Cao; Yihao Wei; Yaohang Yue; Peng Liu; Hui Zeng (Heliyon, 2023)
Over the past 11 years, mounting evidence has suggested a significant association between ferroptosis and the development and progression of musculoskeletal (MSK) diseases, such as osteoporosis and osteoarthritis. However, a comprehensive bibliometric analysis summarizing the relationship between ferroptosis and MSK diseases is currently lacking. The present study collected articles and reviews on the topic of ferroptosis in MSK diseases. The data were collected from January 1st, 2012 to June 30th, 2023 by screening the Web of Science database. Various tools, including VOSviewer, CiteSpace, Pajek, the R package, and others, were used to conduct bibliometric and visualization analyses. Notably, China, the USA, and Italy emerged as primary contributors, jointly accounting for over 80 % of published documents, thereby shaping research in this domain. Among the diverse institutions, Shanghai Jiao Tong University, Soochow University, and Huazhong University of Science and Technology displayed the highest productivity levels. The most prolific authors include Sun Kai, Shang Peng, and Jing Xingzhi. Oxidative Medicine and Cellular Longevity stood out with the largest number of publications in this area. The five most significant disorders in this field are bone fractures, osteosarcoma, bone neoplasms, joint diseases, and osteoporotic fractures. This study represents an inaugural comprehensive bibliometric analysis, presenting a holistic view of the knowledge framework and developmental patterns in ferroptosis concerning MSK diseases over the previous eleven years. This information can aid researchers in acquiring a thorough grasp of this domain and offer invaluable insights for forthcoming explorations.